Calciphylaxis: Temporal Artery Calcification Preceding Widespread Skin Lesions and Penile Necrosis - Manzoor A. Shah; Michael W. Roppolo (Case Reports in Nephrology)
Temporal artery calciphylaxis has rarely been described in chronic kidney disease patients on dialysis. We report a case of 72-year-old Caucasian man with multiple comorbidities and end-stage renal disease on dialysis who presented with temporal artery calcification leading to bilateral loss of vision followed by extensive skin lesions including one on glans penis. While on peritoneal dialysis, he developed anterior ischemic optic neuropathy, had no improvement on high dose steroids, and temporal artery biopsy showed marked calcification without any evidence of vasculitis. Few weeks later on hemodialysis, he developed widespread cutaneous lesions on extremities and penile necrosis with skin biopsy revealing calciphylaxis. On literature review of calciphylaxis in chronic kidney disease, we found only four cases of temporal artery calciphylaxis leading to anterior ischemic optic neuropathy and blindness. We believe this is the first case in which the rare temporal artery calciphylaxis and the uncommon penile necrosis are being described together. The objective is to emphasize the need to recognize this condition early in the CKD patients on dialysis presenting with visual symptoms as the different treatment strategies may help prevent complete loss of vision and also modify or prevent a full blown calciphylaxis.